2010
DOI: 10.1007/s10517-010-1087-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Mesenchymal Stem Cells Labeled with Magnetic Microparticles in Vitro and Analysis of Their Distribution after Transplantation

Abstract: Mesenchymal stem cells enzymatically isolated from human placenta were labeled with magnetic fluorescent microparticles (d=0.96 μ). We showed that microparticles in high doses (>10 μl stock suspension per 1 ml culture medium) significantly inhibited cell proliferation in culture. In our work we determined the optimal concentration of particles not affecting physiological properties of mesenchymal stem cells: it does not change cell proliferation, does not induce apoptosis, and does not modulate their transdiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Earlier we have shown that labeled hMSCs retained the SPIO microparticles for at least four weeks [ 33 ]. Moreover, labeling did not noticeably affect the cells’ ability to undergo osteogenic, chondrogenic, adipogenic, and neurogenic differentiation in vitro [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier we have shown that labeled hMSCs retained the SPIO microparticles for at least four weeks [ 33 ]. Moreover, labeling did not noticeably affect the cells’ ability to undergo osteogenic, chondrogenic, adipogenic, and neurogenic differentiation in vitro [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since MSCs of different origin possess high migration ability and can undergo homing in various tissues and organs [47,48], expression of adhesion molecules on the cell surface represents an important phenotypic characteristic of these cells. To reach the parenchyma of the organ after systemic administration, MSCs should behave like leukocytes do during inflammation.…”
Section: Morphology and Phenotype Of Human Liver Mscsmentioning
confidence: 99%
“…Cultured skin fibroblast-like cells contain subpopulations capable of differentiation within and out of the boundaries of the mesodermal lineage: into adipocytes, osteoblasts, chondrocytes, smooth muscle cells, neurons, astrocytes, and insulin-producing cells. 109 , 112 , 116 120 Cultures of skin plastic adherent cells contain cells originating from different structures forming this complex organ including dermis, adipose tissue, hair follicles, sweat and sebaceous glands, and others. It should be noted that fibroblast-like cells derived from skin specimens taken from the skull are partly of ectoderm origin because during embryogenesis in this area dermis is formed from the neural crest.…”
Section: Hepatogenic Differentiation Of Ipscmentioning
confidence: 99%